Conservation of Sarawak peat swamp in an urban landscape by fuzzy inference system - Mah, D.Y.S. (Springer-Verlag, 2011)
Freshwater habitats are one of the planet’s most important, yet most manipulated, environments. This is what happens in Sarawak that the environment has been radically changed due to urban developments. This paper is promoting the idea that we do not need a complicated but a simple tool like fuzzy inference system to strike a balance between the existence of peat swamp and the humans who live nearer and nearer to it. Conditions vital to the survival and continuity of a natural wetland system can be adapted as fuzzy rules. These rules are capable of providing indicators of how much wetland can be exploited and at the same time still allow the system to properly functioning as a wetland.